Implementasi pendidikan karakter melalui mata pelajaran Pendidikan Pancasila dan Kewarganegaraan pada SMA Lokon St. Nikolaus Tomohon - Sampul, Alfarani Sindi; Kerebungu, Ferdinand; Lonto, Apeles Lexi (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
This Study aimed to describe the implementation of character education through Pancasila and Civics Education subject at SMA Lokon St. Nikolaus Tomohon, its driving and inhibiting factors. The implementation was done based on Pancasila Student Profile, school motto, and curriculum guidelines document. Character education through Pancasila and Civics Education subject was implemented in three stages: 1) Preparation stage: lesson plan and learning contract. 2) Implementation stage: curricular and extracurricular acitivies. 3) Evaluation stage: documentation and assesment. There were some driving and inhibiting factors. Driving factors of the implementations were boarding school system, teachers engagement, values of character were integrated with the subject’s content, method, learning environtment, and teacher’s creativity to help students solve their difficulties. Meanwhile, the inhibiting factors were some students lack of motivation to learn and teacher was lack of ability to use real life experience as a learning media. This study provided several recommendations: 1) Teacher needed to improve the planning of character education through Pancasila and Civics Education subject, such as prioritizing character’s values, describing each value’s indicators practically and measurable, choosing assesment method and its instrument. 2) Teacher and students needed to follow the learning contract they made together consistently. 3) All school stakeholders needed to cooperate regularly and consistently, 4) Teacher needed to improve her/his teaching skills by following training or worskhop organized by school management or by other institution.